Modelling of reduced electromechanical interaction system for aircraft applications. Issue 7 (11th June 2019) - Ahumada, Constanza; Wheeler, Pat
Abstract : Rotational systems such as aircraft engine drivetrains are subject to vibrations that can damage shafts. Torsional vibrations in drivetrains can be excited by the connection of loads to the generator due to electromechanical interaction. This problem is particularly relevant in new aircraft because the drivetrain is flexible and the electrical power system (EPS) load is high. To extend the lifespan of the aircraft engine, the electromechanical interaction must be considered. Since real‐time constants of the electrical and mechanical systems have very different magnitudes, the simulation time can be high. Furthermore, highly detailed models of the electrical system have unnecessary complexity for the study of electromechanical interactions. For these reasons, modelling using reduced order systems is fundamental. Past studies of electromechanical interaction in aircraft engines developed models that allow the analysis of the torsional vibration, but these are difficult to implement. In this study, a reduced order electromechanical interaction system for aircraft applications is proposed and validated using experimental results. The proposed system uses a reduced drivetrain, simplified EPS, and sensorless measurement of the vibrations. The excitation of torsional vibrations obtained is compared with past studies to prove that the reduced order system is valid for studying the electromechanical interactions.